Emission tax revenues in a growing economy - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1997)
This paper focuses on how emission tax revenues change relative to GNP, when a fixed environmental standard is implemented by an emission tax and when waste abatement, technical and structural change and capital accumulation is accounted for. One- and two-sector growth models are analyzed allowing for demand substitution and sectoral differences in emission intensities and elasticities of technical substitution. It turns out that the more difficult it is to reduce the emission of pollutants either by abatement or by shifting the demand towards low-pollution goods the more likely emission taxes are reliable long-term sources of tax revenues.
Keywords: 330